A Rare Case of Multifocal Prostatic Blue Nevus. (21st February 2018) - Farran, Elias J.; Kerr, Preston S.; Kosarek, Christopher D.; Sonstein, Joseph; Eyzaguirre, Eduardo J.
Abstract : Prostatic blue nevus is a rare benign pathologic diagnosis most commonly diagnosed incidentally on many different types of prostate specimens. Blue nevus is the deposition of stromal melanin characterized by spindle cells within the fibromuscular stroma which stains positive for melanin-specific stains Fontana-Masson and S100 and stains negative for CD68, HMB45, and iron stains. We report the case of a multifocal and bilateral blue nevus in a 52-year-old Hispanic male who presented with an elevated prostate-specific antigen of 4.3 and mild obstructive lower urinary tract symptoms, found by transrectal ultrasound-guided prostate needle biopsy. The biopsy also revealed benign prostatic tissue with postatrophic hyperplasia and chronic inflammation. This is the 35th reported case of prostatic blue nevus and the third to show multifocal blue nevus.